PDF Design Optical BPF Using Double Clad Fiber MZI for Free Space Optical Communication: Mohanad G. Khamees , Tahreer S. Mansour* - Alhasani, Mohanad; tahreer (Iraqi Journal of Laser, 2022)
Abstract: A novel design of Mach Zehnder Interferometer (MZI) in terms of using special type of optical fiber that has double clad with graded distribution of the refractive index that can be easily implemented practically was suggested and simulated in this work. The suggested design is compact, rapid, and is simple to be modified and tested. The simulated design contains a MZI of 1546.74 nm of central wavelength that is constructed using special type of double clad optical fiber that has two different numerical apertures. The first aperture will supply single mode propagation via its core, while the second numerical aperture supports a zigzag wave propagation (multimode) in the first clad region. The interferometer’s sensing arm (double clad fiber) was etched using 40% Hydro-Fluoric (HF) acid to achieve three different fiber diameters, which are ( 84, 72, 54 ) µm with ( 5 ) cm length. The simulation programs Optiwave version 15 and Optigrating version 4.2.2 were used to simulate the setup and to acquire the readings for the three durations of etching (10, 20, and 30) min, and also for the case of no etching at all. The obtained results show that the simulated setup can be used efficiently to test which one of the etching cases has the highest effect on the performance of the overall system, specifically when it comes to spectrum bandwidth, signal amplitude, and received power. The simulated design contains a MZI of 1546.74 n. meter of central reflection wavelength that is constructed from different types of optical fibers. The used Double Clad (DC) optical fiber diameter was reduced in 3 steps as if it was etched using Hydro-Fluoric (HF) acid to achieve three additional different diameters, which are (84, 72, 54) µ. meters in addition to the default 125 µ. meters. The simulation programs (Optiwave and Optigrating) were used to simulate the setup and to acquire the readings for the three durations of etching (10, 20, and 30) min, and also for the case of no etching at all. The obtained results show that the simulated setup can be used efficiently to test which one of the etching cases has the highest effect on the performance of the overall system, specifically when it comes to spectrum bandwidth, signal amplitude, and received power.